Dampak Kampanye Media Sosial Instagram dalam Mengubah Sikap Generasi Z terhadap Isu Politik - Galuh Febriyanti; Achmad Nashrudin Priatna; April Laksana; Rizqi Fitrianti; Arfian Suryasuciramdhan (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2026)
The development of digital technology has fundamentally changed political communication patterns, especially among Generation Z who grew up in a social media ecosystem. This study aims to analyze the influence of political campaigns through Instagram on changes in political attitudes of students at the Faculty of Social and Political Sciences at Bina Bangsa University. This study uses an explanatory quantitative approach. Data collection techniques were carried out through a survey using a closed questionnaire, which was distributed to 100 respondents. Data were analyzed using a simple linear regression test with the help of SPSS software version 25. The results of the study indicate that political campaigns on Instagram have a significant influence on changes in students' political attitudes. The dimensions of attitudes influenced include attention to issues, understanding of political messages, and acceptance of certain ideas or figures. Based on these findings, it can be concluded that credible, relevant, and communicative digital campaigns have great potential in shaping the political orientation of Generation Z. Therefore, adaptive communication strategies are needed as well as strengthening political and digital literacy among students to encourage more critical and responsible political engagement.